On the graphics of metal arches with special reference to the relative strength of two-pivoted, three-pivoted and built-in metal arches - Atcherley, L. W. (Drapers' company research memoirs. Technical series, 1905)
Chapters include case studies of two-pivoted, three-pivoted and doubly built-in arches.